Supraventricular Tachyarrhythmias in Patients with Ebstein’s Anomaly - Stychynskyi, O. S.; Almiz, P. O.; Topchii, A. V.; Plyska, N. V.; Pokanevich, A. V.; Kovalchuk, A. V. (Ukrainian Journal of Cardiovascular Surgery, 2019)
The paper analyzes the experience of catheter treatment of various types of supraventricular arrhythmias in patients with Ebstein’s abnormality (EA) – 19 consecutive cases of the elimination of additional atrioventricular connections (AAVC) and 5 cases of atrial macro-reentry. The elimination of AAVC, just like atrial macroreentry, was preceded by a stage of electrophysiological diagnosis. In a series of observations in 19 patients with EA, 25 AAVC were detected. The article reflects the main electrophysiological differences between “wide” AAVC from multiple ones. In the first procedure, the conduction in all AAVC was eliminated in 16 (84.2%) of 19 patients. 6 of 25 AAVC were qualified by us as “wide”; to eliminate them, a larger number of applications was required – 6 ± 2 (in typical cases – 3 ± 1). In 2 of 3 patients with an unsatisfactory result of the first procedure, AAVC were eliminated during the second procedure. In the long-term period(5.6 ± 3.6 years), recurrences of propagation through AAVC occurred in 2 (10.5%) of 19 patients. All AAVC were permanently eliminated during second procedure. In the group of patients with atrial tachycardia, 3 had a graph characteristic of a typical isthmus-dependent atrial flutter. In one patient with atypical graphics, macro-reentry with excitation circulation around the scar on the anterolateral wall of the right atrium was found. In 3 of 4 patients with isthmus-dependent atrial flutter after radiofrequency exposure, the sinus rhythm was restored and a block of passage through the cavotricuspid isthmus was created. In one case there were changes in the cycle of tachycardia and the morphology of wave P, applying applications between the scar and the tricuspid valve ring led to the creation of a block of passage through this area and to the cessation of arrhythmia. In a patient who initially had reentry with a circulation of excitement around the postoperative scar, arrhythmia was eliminated in a similar way (an additional block was created through the cavotricuspid isthmus). In the observation period of 5.2 ± 2.5 years, there were no recurrences of arrhythmia.